A systematic review of interventions for emotionally dysregulated children - Timakwe, Ayabonga Mbalentle (University of Cape Town, 2021)
Emotion regulatory problems in children, such as uncontrollable tantrums, kicking, and screaming, are a concern for parents. When parents and caregivers have no tools at their disposal to deal effectively with this, they may resort to physical measures of discipline, which may lead to physical abuse and also have negative effects on the wellbeing of the child. There is a need for a set of skills for what to do during these crisis moments. However, the state of evidence on this is unknown. Thus, a systematic review of interventions for emotionally dysregulated children was conducted in order to ascertain the state of evidence and to provide parents, teachers, hospital staff and caregivers with a "toolbox" of skills they can use. The findings of the studies indicated that the skills worked when used in a noncoercive manner. Overall the quality of the studies was weak: most were single-case studies. This review provides tentative suggestions of skills that parents and caregivers may find useful with dysregulated children, but further research into the effectiveness of these skills is needed.